2021
DOI: 10.1186/s12877-021-02280-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Psychometric Properties of PainChek® in UK Aged Care Residents with advanced dementia

Abstract: Background The aim of this study was to further validate PainChek®, an electronic pain assessment instrument, with a population living with dementia in a UK care home. Method This study utilised a correlational design to evaluate the psychometric properties of PainChek® when compared to the Abbey Pain Scale (APS). Blinded paired pain assessments were completed at rest and immediately post-movement by a researcher and a nurse. A total of 22 particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Despite the most recent update of these guidelines being in 2009, they remain relevant to current approaches to assessing pain in this population. They are recognised as the basis to observational pain assessment tools, as reflected in more recent studies and guidelines [ 1 , 6 , 46 ]. However, it is also recognised that the interpretation of these behaviours is complex when applied to dementia.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the most recent update of these guidelines being in 2009, they remain relevant to current approaches to assessing pain in this population. They are recognised as the basis to observational pain assessment tools, as reflected in more recent studies and guidelines [ 1 , 6 , 46 ]. However, it is also recognised that the interpretation of these behaviours is complex when applied to dementia.…”
Section: Resultsmentioning
confidence: 99%
“…Inclusion criteria include: 5) their healthy condition permits the use of a multifunctional pulse oxygen monitor; (6) understanding the meaning of the FPS-R; (7) volunteering to participate in the study and signing the informed consent (caregivers, patients, and/or family members). Exclusion criteria are as follows: (1) moderate or severe dementia; (2) medical contraindication for ear acupressure (in ammation, ulcers, frostbite in the ear); (3) history of allergy to adhesive tape and alcohol; (4) critically ill patients who have no response to the effectiveness and safety of new treatments (serious heart, brain, liver, kidney, or hematopoietic system diseases) (5) patients who received drugs for pain management.…”
Section: Patientsmentioning
confidence: 99%
“…It is estimated that prevalence of pain in dementia patients residing in the nursing home is 19%-83% and pain they are suffering is di cult to assessed and inadequately treated [2][3][4]. There is also guideline that indicates that the incidence of acute pain is as high as 75% in elderly care facilities, but even higher for chronic pain [5]. Furthermore, uncontrolled pain causes many detrimental consequences for patients with dementia in nursing homes, such as distressing psychological, social isolation, daily activity and function limitation, sleep disturbances, hospital stays prolonging and medical expenses increasing [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Pain is the most common complaint of residents with dementia in nursing homes. e prevalence of pain among residents is significantly higher than in other communities, with numerous studies indicating that as many as 40% to 80% of these residents with dementia were affected by pain [4][5][6]. A study in Europe reported that up to 82.9% of senior citizens with dementia experience pain in the nursing home [7].…”
Section: Introductionmentioning
confidence: 99%